PENGARUH PENGGUNAAN FITUR PAYLATER TERHADAP PERILAKU IMPULSIVE BUYING PADA MAHASISWA PENGGUNA E-COMMERCE DI KOTA BANDAR LAMPUNG - Diva Amanda; Yusuf S Barusman (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2025)
The purpose of this research is to find out how students in Bandar Lampung who use e-commerce and make impulsive buying when using the Paylater option. Paylater, a digital credit-based payment option, is growing in popularity and may influence impulsive buying. This study examines the impact of Paylater on impulsive buying behavior through a quantitative approach using a simple linear regression method. A total of 97 students in Bandar Lampung City who regularly shop online became the sample of this study. The regression test results show that the use of Paylater significantly and positively affects impulsive buying behavior, with a coefficient of 0.719 and a p-value of 0.000. Because the p-value of paylater is smaller than 0.05 (0.000), the t-value is 14.077> 1.985. Payletter seems to have an important and beneficial effect on impulsive buying. Paylater accounts for about 67.6% of the variance in impulsive buying, corresponding to an R² value of 0.676. Finally, students in Bandar Lampung City who use e-commerce and utilize the paylater feature are less likely to make impulsive buying.